Lipid Profile Analysis Of Coronary Heart Disease Patients In Gatot Soebroto Indonesia Army Central Hospital For January-June 2024 Period - Ineke Putri Anata; Intan Farida Yasmin (Green Publisher Indonesia, 2025)
Coronary Heart Disease (CHD) remains a leading cause of death globally. The accumulation of plaque in the coronary arteries, frequently triggered by lipid deposition, is a primary contributor to CHD. Lipid profiles serve as crucial indicators for assessing risk and monitoring treatment response in CHD patients. This study aimed to analyze the lipid profiles of patients diagnosed with CHD at the RSPAD Gatot Soebroto heart clinic. This was a quantitative descriptive observational study. The sample comprised 84 CHD patients whose diagnosis was confirmed through EKG, coronary CT scan, or angiography. Measured variables included total cholesterol, triglycerides, High Density Lipoprotein (HDL), and Low Density Lipoprotein (LDL). Results indicated that 38.6% of patients had one-vessel disease, and over half of the sample was under 60 years old. While a majority of patients had normal levels of triglycerides (64.3%), total cholesterol (64.3%), and HDL (53.6%), a substantial proportion (63.1%) exhibited abnormal LDL levels. This study demonstrates that, despite many CHD patients having normal lipid profiles, a significant proportion still presents with abnormal LDL levels. Further research is necessary to identify the factors contributing to abnormal lipid profiles in CHD patients and to evaluate the efficacy of interventions aimed at improving lipid profiles.